Improving Critical Thinking Skills Using the Guided Inquiry Learning Model Assisted by Interactive Modules on Elasticity Material - Nursabrina, Fakhira; Hasanah, Halimah Al; Astra, I Made (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2024)
This research aims to evaluate the effectiveness of the guided inquiry learning model with the help of interactive modules in improving students' critical thinking skills on elasticity material. This research was conducted involving 39 students of class XI MIPA 5 at a high school in Tangerang Regency. The research model used is Classroom Action Research Action Research using the Kemmis & McTaggart model . The research results showed a significant increase in the critical thinking abilities of students who used the guided inquiry learning model with interactive modules with results obtained in interpretation of 88%, analysis of 63%, evaluation of 93%, and inference of 89%. So it can be concluded that improving critical thinking skills using the guided inquiry learning model assisted by interactive modules on elasticity material results in an increase in the high category.